2014
DOI: 10.5194/hess-18-4207-2014
|View full text |Cite
|
Sign up to set email alerts
|

Small farm dams: impact on river flows and sustainability in a context of climate change

Abstract: Abstract. The repetition of droughts in France has led to a growing demand for irrigation water and consequently to an increase in requests for the construction of small farm dams. Although such dams are small, their accumulation in a basin affects river flows, because the water collected in these small farm dams is used for irrigation and thus does not contribute to river flow. In order to gain more insight into their impact on the annual and monthly discharges, especially during dry years, a small farm dam m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 34 publications
1
15
0
1
Order By: Relevance
“…To date, the relatively few regional studies on small, artificial water bodies (hereafter "ponds") have focussed on water and sediment dynamics rather than GHG emissions (Downing et al, 2008;Callow and Smettem, 2009;Verstraeten and Prosser, 2008;Habets et al, 2014). Studies of GHG emissions from ponds have been limited (Downing, 2010;Deemer et al, 2016) but are in agreement with assessments of larger water bodies where CH 4 is the dominant GHG relative to N 2 O and CO 2 (Merbach et al, 1996;.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…To date, the relatively few regional studies on small, artificial water bodies (hereafter "ponds") have focussed on water and sediment dynamics rather than GHG emissions (Downing et al, 2008;Callow and Smettem, 2009;Verstraeten and Prosser, 2008;Habets et al, 2014). Studies of GHG emissions from ponds have been limited (Downing, 2010;Deemer et al, 2016) but are in agreement with assessments of larger water bodies where CH 4 is the dominant GHG relative to N 2 O and CO 2 (Merbach et al, 1996;.…”
Section: Introductionmentioning
confidence: 88%
“…These water bodies provide valuable services and are required to irrigate crops, provide water for farm stock, manage storm water, offer visual amenity and recreational activities, and supply water for industrial processes (Fairchild et al, 2013). Small water bodies are often avian biodiversity hotspots, for example hosting an estimated 12 million water birds in a single catchment area in the Murray-Darling river system, Australia (Hamilton et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, widespread river regulation in temperate regions may limit natural high‐ and low‐flow extremes, with compensation flows released from impoundments maintaining a minimum discharge that reduces intermittence. Agricultural land use can also reduce hydrological variability and cause artificial perennialization; for example, small agricultural dams release water downstream at a steady rate for irrigation …”
Section: Interacting Stressors Compromise Temporary Stream Healthmentioning
confidence: 99%
“…More sophisticated downscaling methods could not be applied here because the meteorological record was too short. However, previous studies indicated that the main uncertainty in climate change impact studies is associated with the GCM (e.g., Habets et al, 2013). Temperature and precipitation anomalies were extracted from the output of the SCAMPEI project climate models (http://www.cnrm.meteo.fr/ scampei/).…”
Section: -D and 2-d Validation Of Snowmodelmentioning
confidence: 99%